E-S-Qual and E-Recs-Qual Toward Customer Satisfaction, Trust and Loyalty in Electronic Banking Services During The Covid-19 Pandemic - Ramadania, Ramadania (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2021)
During the pandemic, many countries adopted physical & social distancing policies, lockdowns, or territorial quarantine. Therefore the use of electronic banking services has increased sharply, including in developing countries such as Indonesia. Electronic banking services that are popularly used by many customers are in the form of internet banking and mobile banking. This study aimed to analyze; 1) the impact of the core online service quality (E-S-QUAL) on customer satisfaction, 2) the effect e-recovery service quality (E-RecS-QUAL) on satisfaction, 3) the effect of satisfaction on customer trust and 4) the effect of trust on customer loyalty. This research is causality research or explanatory research. The data collected by survey method to 120 respondents from customers who are registered users of e-banking (i.e. internet banking or mobile banking) from Mandiri, BCA, and Bukopin Bank. The results showed that the core online service quality (E-S-QUAL) and e-recovery service quality (E-RecS-QUAL) proved to have a positive influence on customer satisfaction. This research also proves the strong positive relationship between satisfaction and trust, as well as trust also has been shown to have a strong influence on customer loyalty .